2022
DOI: 10.1111/ijfs.15995
|View full text |Cite
|
Sign up to set email alerts
|

Consumer perception of insects as food: Mexico as an example of the importance of studying socio‐economic and geographical differences for decision‐making in food development

Abstract: Mexico is a multi-diverse country where insect consumption has been associated with traditional practices. Nevertheless, there are no studies regarding differences in entomophagy within the country to get specific insights into consumers' perceptions. A total of 3125 Mexicans answered a national survey related to demographic indicators and aspects of edible insects. The v 2 test was used (P < 0.05) to analyse the data. Results showed that a national average of 74% had consumed insects, mainly from the south an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…However, not all Mexican populational groups are entomophagous, and there are areas where consumers also do not have a tradition of eating insects. The work by Escalante-Aburto et al [ 45 ] refers that Mexico is a multi-diverse country with some tradition of entomophagy, but differences were encountered within different regions of Mexico; in the south and centre, people consume more EIs, while in the north, the practice is not so usual. A study by Gómez-Corona et al [ 46 ] revealed that some Mexican citizens are insect eaters and others are not, but the representation that they have about EIs is similar nonetheless.…”
Section: Discussionmentioning
confidence: 99%
“…However, not all Mexican populational groups are entomophagous, and there are areas where consumers also do not have a tradition of eating insects. The work by Escalante-Aburto et al [ 45 ] refers that Mexico is a multi-diverse country with some tradition of entomophagy, but differences were encountered within different regions of Mexico; in the south and centre, people consume more EIs, while in the north, the practice is not so usual. A study by Gómez-Corona et al [ 46 ] revealed that some Mexican citizens are insect eaters and others are not, but the representation that they have about EIs is similar nonetheless.…”
Section: Discussionmentioning
confidence: 99%
“…Las cuetlas o xonocuilín (Arsenura armida) se ingieren únicamente e n larvas, en: Hidalgo, Oaxaca, Puebla y Veracruz. Los chinicuiles o gusano rojo de maguey (Aegiale hesperiaris) se consumen solo en larvas y se ingieren mayormente en el Estado de México, Ciudad de México, Hidalgo, Michoacán, Oaxaca, Puebla, Querétaro, Tlaxcala y Veracruz; del gusano blanco de maguey (Commadia redtembacheri) también se ingieren las larvas y son mayormente consumidos en el Estado de México, Ciudad de México, Hidalgo, Durango, Guanajuato, Michoacán, Oaxaca, Puebla, Querétaro, Tlaxcala y Zacatecas (Escalante-Aburto, et al, 2022). Del axayácatl (Corisella mercenaria S.) se consume la fase adulta y a sus huevecillos se les llama ahuautle; es ingerida en Chiapas, Estado de México, Ciudad de México, Hidalgo, Guanajuato, Michoacán, Oaxaca, Querétaro y Tlaxcala.…”
Section: Coleóptera Insectos Comestibles De Méxicounclassified
“…In addition, the rapidly growing human population has increased the demand for protein quantities, thus, the consumption of insects as an alternative protein source is considered a future trend that has the potential to improve global food security (de Castro et al 2018;Lu et al 2022a). Across the world, a large population of humans consume insects as a regular part of their diet, including some countries from Latin America, Africa, Asia and Oceania (Mancini et al 2019;Escalante-Aburto et al 2022). Consumer acceptance and perception of edible insects continues to be hindered by prevalent disgust responses and aversion.…”
Section: Introductionmentioning
confidence: 99%